The Impact of the Influx of Illegal Chinese Workers in Indonesia on Indonesia's Relationship with China - Elisa, Stephanie; Utomo, Tri Cahyo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The influx of illegal Chinese workers has resulted in violations against the Indonesiangovernment regulations such as the Immigration, Ministry of Manpower, and Ministry ofLaw and Human Rights in Indonesia. The method of this research is using qualitativeresearch that explains about how is the impact between the relationship with Indonesia andChina of the entry of illegal foreign workers from China on Indonesia from 2015 until2017. Furthermore, this impact is being analyzed by using Neoclassical theory andRational Choice theory. Finally within this resarch it has been found that, Indonesia stillneeds economic improvement from various foreign investors especially from Chinabecause the Indonesian State Budget has not reached the target of state infrastructuredevelopment. So far, the action that Indonesia can take rationally is to maintain it's goodrelations with China, for now and in the future. Therefore, Indonesia is still committed onrevising its regulations and policies to improve its procedures in the employment andsupervision of foreign workers in Indonesia that is in the sectors of the Immigration, theMinistry of Manpower, and the Ministry of Justice and Human Rights in Indonesia.